The association of preoperative dialysis with troponin trends and short term outcomes among advanced kidney disease patients undergoing coronary artery bypass grafting. (4th February 2022) - Manla, Y; Hogan, M; Bhatnagar, G; Khan, N; Alsindi, F; Aljabery, Y; Sanger, S; Gobolos, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Coronary artery disease continues to be the leading cause of death in patients with stage IV-V chronic kidney disease (CKD IV-V). However, the prognosis and early outcomes for advanced CKD patients undergoing coronary artery bypass grafting (CAB) worsen as the estimated glomerular filtration rate (eGFR) deteriorates. Therefore, we compared postoperative clinical outcomes and troponin trends in patients having advanced CKD according to preoperative dialysis status in a single centre experience. Methods: A total of 51 patients with CKD IV and V who underwent CAB between 2016-2021 were included in the study. Data on patient characteristics and postoperative outcomes were collected retrospectively, and independently for our Society of Thoracic Surgeons database. Characteristics were compared between patients having CKD IV vs. CKD V. The differences in postoperative cardiac troponin trends and outcomes were evaluated between patients who did vs. did not undergo preoperative dialysis. The statistical analysis was conducted applying appropriate parametric or non-parametric (for skewed variables) testing methods, and a p value < 0.05 was considered to be statistically significant. Results: 47% (24) of subjects had CKD IV, while the rest featured CKD V. Patients with CKD IV tended to be older (61.8 ± 9.2 vs. 56.3 ± 11.5 years, p = 0.07), more obese (BMI: 31.4 ± 6.8, 27.4 ± 4.9 kg/m2, p = 0.02) and had significantly higher preoperative GFR (23 ± 4.9 vs. 9 ± 3.3 mL/min, p < 0.001) (Table.1). When comparing patients who underwent preoperative dialysis vs. those who did not, troponin levels were the highest at 18h postoperative in both groups, however, troponin levels were comparable between both groups at all time points (Table.2). Although, there was no difference in hospital length of stay and mortality between these groups, patients who did not undergo preoperative dialysis had longer intensive care unit length of stay (ICU LOS). Conclusion: In this single centre experience preoperative dialysis was not associated with a significant difference in trends of postoperative cardiac enzymes. Although preoperative dialysis was associated with shorter ICU LOS, complex pre-procedural surgical risk assessment remains paramount in reducing complications and mortality in this high-risk population.